Evaluation of Non-Compliance Road Furniture on The Road Safety Aspect in the Urban Area. A Case Study of Jalan Kinta District FT001 (Section 606.85 to 607.85) State of Perak Darul Ridzuan - Muhammad Jabri Aqil Johari,; Abd Rahman, Ir. Ts. Dr. Raha; Mohd Haizman Hakim Abdullah,; Nurul Akmar Mohamad Ramli,; Meor Mohamad Haris Meor Hussein,; Jezan Md Diah, (Recent Trends in Civil Engineering and Built Environment, 2025)
Over 2016-2023, road crash data in Malaysia exhibited a consistent upward trend, with a temporary decline during the COVID-19 pandemic attributed to reduced road users. This study investigates non- compliance road furniture and analyses its correlation with road accidents   in   Perak,  Malaysia,  along  FT001   from   Section   606.85 to 607.85. The study includes spot speed and traffic volume analysis using data from the Malaysian Public Works Department (JKR) Kinta District. Findings indicate that 37% of non-compliance road furniture requires urgent attention. However, weak and statistically insignificant correlations were observed between non-compliance road furniture  and road accidents in the area, supporting previous research by MIROS emphasizing the human factor as the primary contributor to road safety 80% and followed by other factors.